Comparison of elemental resolved non-confined and restricted electrochemical degradation of nickel base alloys. (September 2021) - Dworschak, Dominik; Cheng, Hsiu-Wei; Ku, Ching-Shun; Chiang, Ching-Yu; Lin, Chia-Hsien; Valtiner, Markus
Highlights: With a spectroelectrochemical flow cell the communication of the crevice enables studying solution chemistry in confinement. Degradation in a crevice is compared to freely-exposed conditions by dissolution profiles and surface composition. Mo forms stable passive Mo(VI) layers under open corrosion, while it remains soluble under crevice conditions. Abstract: Passive film properties of nickel base alloys (NBAs) have been studied extensively, yet elemental resolved dissolution currents under corrosive conditions are less well studied. Here, we compare elemental dissolution currents during anodic polarisation and repassivation under crevice and freely-exposed conditions for various NBAs using an ICP-MS flow-cell approach. With a new sample design we can track communication of a crevice environment with the electrolyte, providing insight into crevice solution chemistry and solubility of passive film-forming elements. Data indicates Mo can only form stable precipitate layers under openly corroding conditions. Local elemental depletion was further examined by XPS and nanometer resolved XRF.